PENGARUH DOMINAN CASH RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON EQUITY DAN RETURN ON ASSETS PADA PERUSAHAAN TRANSPORTASI DI BURSA EFEK INDONESIA - Yuniastuti, Rina Milyati (Jurnal Manajemen Magister Darmajaya, 2016)
The Purpose of this research is to be achieved is to determine the most dominant influence between casht ratio and debt to asets ratio toward return on equity and return on Assets to transportation companies on the stock exchange Indonesia.In the research to provide information will be the dominant influence is cash ratio and debt to assets ratio to return on assets.This is because the cash ratio and debt to assets ratio and return on assets indicate how much contribution the companys assets. Â Keyword: dominant influence, cash ratio, debt to asset ratio, return on equity, return on assets